ОСОБЕННОСТИ ВЛИЯНИЯ ФАКТОРОВ РИСКА НА ФОРМИРОВАНИЕ АТЕРОСКЛЕРОЗА У ЛИЦ С НЕДИФФЕРЕНЦИРОВАННОЙ ФОРМОЙ ДИСПЛАЗИИ СОЕДИНИТЕЛЬНОЙ ТКАНИ В ВОЗРАСТЕ 45-60 ЛЕТ - Г. И. Нечаева; И. Ю. Калинина (SINAPS LLC, 2014)
We have fulfilled researches of frequency of atherosclerosis development in different arteries: brachycephalic vessels, abdominal aortic branch among 66 patients at the age of 45-60 with undifferentiated form of dysplasia of connective tissue (UDCT) compared with the group of 31 patients without dysplasia. We have revealed risk factors which influence extremely on origin and development of atherosclerosis: smoking, age, arterial hypertension grade III, left ventricular hypertrophy, underweight body.